2020
DOI: 10.3390/atmos11080829
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variations in Extreme High–Temperature Events over Southern China in the Early 2000s and the Influence of the Pacific Decadal Oscillation

Abstract: This study documents a sudden interdecadal variation in the frequency of extreme high–temperature events (FEHE) over southern China during summer in the early 2000s, which is characterized by a relatively small (large) FEHE during 1991–2000 (2003–2018). The composite analysis on the extreme high–temperature events (EHEs) over southern China indicates that the occurrence of EHEs is mainly influenced by increased downward surface net shortwave radiation, which is induced by the cloud–forced radiation anomalies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…At lag zero, a negative correlation is observed between PDO and ERA‐SAT. The same PDO spatial pattern against the observed SAT in Figure 2d is notable in Figure 3d, consistent with Wang et al (2017) and Zhu et al (2020).…”
Section: Resultssupporting
confidence: 91%
“…At lag zero, a negative correlation is observed between PDO and ERA‐SAT. The same PDO spatial pattern against the observed SAT in Figure 2d is notable in Figure 3d, consistent with Wang et al (2017) and Zhu et al (2020).…”
Section: Resultssupporting
confidence: 91%
“…You et al (2017) showed that the FEHEs based on relative and absolute definitions has increased over the whole of China, particularly after 1990, reflecting rapid warming after this time. Superimposed on these long-term trends, there are also dominant interdecadal and interannual spatiotemporal variations in FEHEs over eastern China (Zhu et al, 2020b;Hong et al, 2020;Liu et al, 2021;Yang et al, 2021;Zhu et al, 2022). The interannual variability of FEHEs is relatively large over eastern China, which greatly contributes to the overall variability Deng et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Eastern China is vulnerable to EHEs, which show a large variability in this region (Sun et al, 2014;Deng et al, 2019). Previous studies have shown that the frequency of EHEs (FEHEs) over China is characterized by variability on different timescales (You et al, 2017;Zhu et al, 2020b). You et al (2017) showed that the FEHEs based on relative and absolute definitions has increased over the whole of China, particularly after 1990, reflecting rapid warming after this time.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the tropical Pacific SSTA have impacts on the summer temperature and EHEs variability over Eurasia by exciting extratropical teleconnection patterns (Behera et al., 2013; Luo et al., 2020; Luo & Lau, 2020; Ming & Sun, 2021). In terms of the interdecadal variations in summer Eurasian EHEs, the PDO is considered as an important driver (Schubert et al., 2014; Yang et al., 2021; Zhu, Sun, Li, & Wang, 2020). In addition to the Pacific, the SSTA in other regions, such as the North Atlantic (Cassou et al., 2005; Della‐Marta et al., 2007; Deng et al., 2019; Sun, 2014) and the Indian Ocean (Chen et al., 2019; Wei et al., 2020; Zhu et al., 2022), can also contribute to the summer Eurasian EHEs variability.…”
Section: Introductionmentioning
confidence: 99%